Selective isolation of ammonia-oxidizing bacteria from autotrophic nitrifying granules by applying cell-sorting and sub-culturing of microcolonies - Fujitani, Hirotsugu; Kumagai, Asami; Ushiki, Norisuke; Momiuchi, Kengo; Tsuneda, Satoshi (Frontiers in Microbiology, 2015)
Nitrification is a key process in the biogeochemical nitrogen cycle and biological wastewater treatment that consists of two stepwise reactions, ammonia oxidation by ammonia-oxidizing bacteria (AOB) or archaea followed by nitrite oxidation by nitrite-oxidizing bacteria. One of the representative of the AOB group is Nitrosomonas mobilis species. Although a few pure strains of this species have been isolated so far, approaches to their preservation in pure culture have not been established. Here, we report isolation of novel members of the N. mobilis species from autotrophic nitrifying granules used for ammonia-rich wastewater treatment. We developed an isolation method focusing on microcolonies formation of nitrifying bacteria. Two kinds of distinctive light scattering signatures in a cell-sorting system enabled to separate microcolonies from single cells and heterogeneous aggregates within granule samples. Inoculation of a pure microcolony into 96-well microtiter plates led to successful sub-culturing and increased probability of isolation. Obtained strain Ms1 is cultivated in the liquid culture with relatively high ammonia or nitrite concentration, not extremely slow growing. Considering environmental clones that were closely related to N. mobilis and detected in various environments, the availability of this novel strain would facilitate to reveal this member’s ecophysiology in a variety of habitats.